Climate Smart Villages in Vaishali district of Bihar - Sharma, S. N. (Indian Farming, 2017)
One of the several interventions of climate smart agriculture has been mungbean inclusion in the cropping pattern. Mungbean has shown to outperform the traditional farmers practice in the area. Mungbean, a prominent short duration crop of the summer season, has been cultivated by the farmers since ages. However, farmers treat this as a crop of minor importance because it has a relatively poor yield potential. Farmers never realized that with improved cultivation practices including the use of improved variety would be a lucrative source of livelihoods. Realizing the potency of good quality seeds of improved variety of mungbean to exploit the fallow period and increase soil fertility, farmers were mobilized to pilot with Pusa Vishal variety of mungbean.